Alih Kode dan Campur Kode dalam Kultum Ustaz Hanan Attaki: Jangan Tinggalkan Salat - Aulya Sarifatil Fitria (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2022)
A seven-minute religious lecture or what is often abbreviated as kultum is a short and concise religious lecture. This research was conducted to examine the events of code mixing and code switching contained in one of UmmaIndonesia's youtube content entitled Kultum Ustaz Hanan Attaki: Don't Leave Salat | umma x detikcom. With qualitative descriptive methods, researchers want to observe more deeply, clearly, and produce data as it is. The data source of this research comes from the Youtube application taken with the note-taking technique, where this technique is done by listening, paying attention, examining the object of research. Furthermore, the data found are recorded and written for analysis. The results of the data analysis carried out are that there are 3 code switching and 6 code mixing in the youtube content. The code-switching and code-mixing event types found fall into the categories of external or outward code-switching and external or outward code-mixing events. This code-switching and code-mixing event is something that often happens in the delivery of religious messages or lectures. Because in his delivery, a speaker must master at least two languages.